THE ROLE OF FINANCIAL SERVICES AUTHORITY IN THE CONSUMER PROTECTION AMID THE GROWTH OF FINTECH INDUSTRY IN INDONESIA - Sari Murti Widiyastuti; Johanes Widijantoro (Fakultas Hukum Universitas Gadjah Mada, 2019)
AbstractThe growth of the financial technology (fintech) industry is a necessity as an effort to make financial services more practical and efficient. On the other hand, consumers of financial services are still low in financial literacy levels, especially in considering various risks that can occur in dealing with the fintech industry. Indonesian Financial Services Authority (OJK) is the body responsible for carrying out the protection of consumers of financial services. This article describes how legal matters in the fintech business, which are actually useful and can encourage financial inclusion, but on the other hand have the potential to harm consumers if they are not properly regulated. Existing related OJK Regulations would be examined and what things should be regulated by the OJK so that consumers of financial services are protected amid the development of fintech, will also be elaborated in this article. This article respectively describes the rationality of consumer protection in the financial services, the dynamics of fintech growth and its problems, and an analysis of the role of OJK in the era of fintech industry. IntisariPertumbuhan industri teknologi keuangan (fintech) adalah sebuah keniscayaan sebagai konsekuensi kemajuan teknologi sekaligus upaya untuk menjadikan jasa keuangan lebih praktis dan efisien. Sementara tingkat “melek keuangan” konsumen masih rendah, khususnya dalam mempertimbangkan berbagai risiko yang dapat terjadi sehubungan dengan layanan fintech. Artikel ini menggambarkan bagaimana persoalan hukum dalam industri fintech di satu sisi, yang sesungguhnya bermanfaat dan dapat mendorong peningkatan derajad inklusi keuangan masyarakat, namun di sisi lain berpotensi merugikan konsumen apabila tidak diatur dengan baik. Apa yang seharusnya diatur oleh Otoritas Jasa Keuangan (OJK) sehingga konsumen terlindungi hak-haknya di tengah pertumbuhan industri fintech, juga akan dianalisis dalam artikel ini.